Epidemiological features of multiple organ dysfunction syndrome in newborns in the Kemerovo region – Kuzbass - A. V. Golomidov; O. G. Kryuchkova; E. V. Grigoriev; A. A. Chernykh; K. V. Lukashov; E. V. Maltseva; V. G. Mozes; K. A. Golomidov; K. B. Moses (Вестник анестезиологии и реаниматологии)
Introduction. Theoretical and practical issues of the short-term and long-term prediction of the onset of multiple organ dysfunction syndrome (MODS) and its outcomes in newborns is a promising area of neonatology, since it allows a doctor to be warned about an impending catastrophe, and opens a «window of opportunity» for timely correction of treatment tactics and prevention of complications.The objective was to study the epidemiological features and medical consequences of multiple organ dysfunction syndrome in full-term and premature newborns born in critical condition.Materials and methods. The stage of retrospective epidemiological analysis was conducted in 2023. The prevalence and outcomes of MODS over a ten-year period (2012–2022) in full-term and premature newborns in the Kemerovo region-Kuzbass were studied.Results. During the period 2012–2022, the mortality rate of children born in critical condition decreased by 2 times, the proportion of patients with MODS and persistent multiple organ dysfunction syndrome (PMODS) decreased, but this phenomenon did not lead to a decrease in the mortality rate of children with developed MODS. In the present study, MODS and PMODS most often developed in extremely immature newborns.Conclusion. Nosologies of newborns with MODS and PMODS were represented by intrauterine generalized infection, congenital pneumonia and, to a lesser extent, cerebral ischemia and congenital malformations.